Young veterans, not always social misfits: a sociological discourse of Liberian transmogrification experiences - Agbedahin, Komlan (Rhodes University, Faculty of Humanities, Department of Sociology, 2012)
This thesis examines the phenomenon of child-soldiering from a different perspective. It seeks to challenge, using a novel approach, earlier studies on the roles of former child-soldiers in post-war societies. It focuses on the subjectivity of young veterans, that is war veterans formerly associated with armed forces and groups as children during the 14-year gruesome civil war which bedevilled Liberia between 1989 and 2003. This civil war claimed roughly 250,000 lives, and saw the active participation of approximately 21,000 child-soldiers. This thesis departs from previous works which mostly painted an apocalyptic picture of young veterans, and explores the nexus between their self-agency, Foucauldian technologies of the self and their transformation in the post-war society. The majority of previous scholarly works which have dominated the field of child-soldiering dwelt on the impact of armed conflict on the child-soldiers, the negative consequences, the causes of child-soldiering, and the rehabilitation and reintegration of the young veterans after their disarmament and demobilization. What this thesis seeks to do however, is to establish that, rather than considering the young veterans simply as social misfits, distraught and dispirited human beings, it should be noted that young veterans through their agency, are capable of ensuring their reintegration into their war-ravaged societies. Sadly, these young former fighters' self-agency and technologies of the self in defining their civilian trajectories have often been overshadowed by vaunted humanitarian aid and multilayered war-profiteering. This study is underpinned by interpretive constructivism, symbolic interactionism, social identity theory, sociometer theory and expectancy theory, and sheds light on how young veterans' self-agency, instrumental coalitions, and decision-making processes, synergistically shifted the negative identities foisted on them as a result of their participation in the war.
Keywords: Child soldiers -- Liberia; Children and war -- Liberia; Liberia. Armed Forces -- Demobilization -- Social aspects; Liberia -- History -- Civil War, 1989-1996; Liberia -- History -- Civil War, 1999-2003